Influence of surgical castration on serum levels of the lipid peroxidation end-products - Baszak, Ewa; Szpringer-Boguń, Ewa; Lutnicki, Krzysztof; Janeczek, Leszek; Rola, Radosław; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2002)
Rationale for the study. The literature contains data suggesting that a postmenopausal woman is exposed to an oxidative stress due to the low estrogen levels. Very scanty data are however available considering the prooxidant-antioxidant homeostasis in the early postoperative period following surgical castration. Objective. The purpose of this study was to characterize the intensity of lipid peroxidation in the perioperative period in premenopausal women who underwent total abdominal hysterectomy with bilateral salpingooophorectomy (TAH&BSO). Patients. Fourty premenopausal women aged 44–55 years were included into this study. The indication for the TAH&BSO was menorrhagia due to uterine fibroids or benign endometrial hyperplasia. Biological material and laboratory analyses. In all the examined patients venous blood was collected before the operation as well as in the postoperative day 2. In the serum samples, level of lipid peroxides was measured, using spectrophotometric TBARs (thiobarbituric acid reactive substatnces) method. Results/Conclusions 1. In the postoperative day 2 levels od lipid peroxidation end-products increase significantly. 2. In the early postoperative period after surgical castration, patients are predisposed to the oxidative stress.